Science and commemoration: a conference on history of domestic special services in the memory of A. M. Plekhanov - A. V. Sushko; D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
An analytical review of the work of the II All-Russian scientific and practical conference «The activities of domestic special services in the era of social cataclysms», held on October 19–20, 2022 in Omsk, is presented. The authors of the publication (active members of the organizing committee) consider the conference as an actual phenomenon of scientific life, which took place in historical foreign and domestic political conditions that are special for Russia. Covered: the course of the event, the main content of scientific reports, key aspects of the controversy, the results of the conference are presented, the resolution is given. The review is addressed to a wide range of readers, including, first of all, researchers of historical science, Russian special services, local history and official commemoration practices.